Examining mediated transfer approach using alice as a teaching tool in object-oriented web programming classes - Abu Seman, Muhamad Sadry; Asyari Sulaiman, Kautsar Taufiqurrahman (Mindware PLT, 2021)
This research aims to investigate the effectiveness of Mediated Transfer Approach using Alice as a teaching tool in improving students' performance in an Object-Oriented Web Programming Class. This study uses a quasi-experiment method with 45 selected participants as a research sample. The number of participants exposed to the Mediated Transfer approach was 20 and referred to as the experimental group, while the other 25 participants were taught by the conventional teaching method and referred to as the control group. They were students from Kulliyyah of Information and Communication Technology (KICT) of International Islamic University Malaysia (IIUM). The teaching approach is examined based on the first three levels of Bloom's Taxonomy, namely Knowledge, Comprehension and Application. The result is shown in two areas; between groups (control and experimental) and within groups (pre-test and post-test). The analysis shows no significant difference between the experimental and the control group (p > 0.05) in Knowledge and Application levels in the between-groups area. However, in the within groups area, the analysis returns a statistically significant improvement from pre-test to post-test (p < 0.05) for the experimental group in all the three levels while in the control group, it was only in the Application level. In conclusion, the students' performance in the experimental group shows a better improvement than in the control group, which indicates that the Mediated Transfer approach is more effective than the conventional method. Hence, it is suggested to adopt the Mediated Transfer approach in programming classes to enhance students' performance.